Study of intestinal stoma: our experience at Rajarajeswari Medical College and Hospital - A., Veena; T. R., Hariprasad; S., Gopal (International Surgery Journal, 2019)
Background: Stoma is an artificial opening of intestinal or urinary tract to the abdominal wall. The purpose of the present study was to identify indications for commonly performed intestinal stomas and to study complications related to it. Methods: This is a retrospective descriptive observational study carried out in a surgical unit of Rajarajeswari Medical College and Hospital, Bangalore from August 2015 to August 2016. Data was collected by previous record files including age, gender, history of presenting illness, indication, type of stoma, type of surgery, appropriate operative findings and follow up of the cases. The results were collected, analysed and compared with other studies. Results: A total of 25 patients were evaluated age ranged between 20-70 years. Out of 25 patients 17 were admitted in emergency while 8 in out-patient department. The most common type of stoma made was loop ileostomy (44%) followed by end ileostomy (28%), end colostomy (16%) and loop colostomy (12%). Main indication for a stoma formation was enteric perforation (56%) followed by carcinoma colon and rectum (32%), perianal sepsis (21%), Koch’s abdomen (11%), penetrating injuries (11%). Of the various complications encountered with intestinal stoma, peristomal skin Excoriation (16%) was the most common complication observed followed by other complications as mentioned in study. Conclusions: In spite of enormous exposure of general surgeons towards stoma formation the complications are inevitable. Early detection of complication and its timely management is the keystone.